Cherenkov Diffraction Radiation From 3D–Printed Dielectric Targets; Electron, Positron, Neutron and X–ray Scattering under External Influences - Bulavskaya A. A. Angelina Aleksandrovna; Alekseev S. V.; Baldin A. A. Anton Aleksandrovich; Bushmina E. A. Elizaveta Alekseevna; Karataev P. V. Pavel Vladimirovich; Kishin I. A.; Klenin A. A.; Kubankin A. S. Aleksandr Sergeevich; Miloichikova I. A. Irina Alekseevna; Polomoshnova D. A. Darjya Anatoljevna; Timoshenko K. D. Konstantin Dmitrievich; Stuchebrov S. G. Sergey Gennadevich (2025, 2025)
Title screen